Evaluation of in vitro starch digestibility and chemical composition in pasta former foods - Vastolo, Alessandro; Cutrignelli, Monica I.; Serrapica, Francesco; Kiatti, Dieu donné; Di Francia, Antonio; Masucci, Felicia; Calabro, Serena (Frontiers in Veterinary Science, 2022)
Former food products include various leftovers from the food industry which, although they have lost values for human consumption, could be safely used for livestock, thus limiting environmental impact of food waste, and reducing feeding costs. The aim of this study was to investigate the nutritional characteristics of different types of former foods from pasta industry. Four types of dry pasta refusal (wholemeal, semolina, purple, and tricolour) and whole barley grain (control) were analysed for chemical composition and in vitro starch digestibility; the energy content was also estimated. For each product type, samples collected in three different times at a pasta plant were analysed. All products showed higher (p<0.001) protein contents and lower (p<0.001) fat contents than barley. The amount of NDF varied between the samples (p<0.001), while all samples reported high starch content (>60% DM). The energy content was higher (p<0.05) in pasta former food compared with whole barley grain. Purple pasta showed different in vitro starch digestibility compared to the other former foods (p<0.001). However, all products showed higher values of resistant starch, whereas barley was mainly composed by slowly digestible starch. The results indicated that dry pasta former foods could be suitable energy sources for feeding pig, but their inclusion in diets must consider the slow digestibility.